Imagination under pressure, 1789-1832 : aesthetics, politics, and utility - Whale, John C. (Cambridge studies in Romanticism, 2000)
This book offers a radical reassessment of one of the most important topics of the Romantic period. John Whale's study of the Romantic imagination focuses on the period's lively and often antagonistic polemics on aesthetics and politics, analysing texts by Burke, Paine, Wollstonecraft, Bentham, Hazlitt, Cobbett and Coleridge.